Three Axis Vibration Measuring Instrument using a Smartphone Display-based Accelerometer Sensor - Theja Lufiandi R; - Yulkifli; Mona Berlian Sari; - Asrizal; - Syafriani (Department of Physics – Universitas Negeri Padang UNP, 2023)
Applications for vibration measurement include machine analysis, measuring vehicle stress, and monitoring building structures. Modern vibration measurement instruments are typically expensive, intricate, and not necessarily readily available to everyone. This research creates and develops a vibration measuring tool that makes use of an accelerometer sensor and a smartphone as a display because of this. Vibration data from the sensor can be transmitted via the Internet of Things, passed through a microcontroller, and then received on a smartphone. This measurement device has the benefits of being simple to use, widely available, and inexpensive. The Four-D (4-D) model is utilized in the Research and Development (R&D) technique. Define, design, develop, and desiminate make up the 4-D approach. A tool that can detect in three dimensions from the x, y, and z axes is the outcome of this research. This tool's design incorporates a smartphone as the display, an ADXL345 accelerometer as a sensor, and a NodeMCU ESP32 microcontroller as a microcontroller. The average accuracy and precision of this tool are 100% and 92%, respectively. It is anticipated that the creation of this measuring tool would expand the accessibility of more effective vibration measurement tools that can be applied in a variety of contexts.